The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/agronomy11061230
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Building Energy Simulation–Life Cycle Assessment (BES–LCA) Approach for Environmental Assessment of Agricultural Building: A Review and Application to Greenhouse Heating Systems

Abstract: A substantial reduction in the environmental impacts related to the construction and operation of agricultural buildings is needed to adapt to the continuing development of agriculture. The life cycle assessment (LCA) is a methodology used to quantify the environmental impact of different processes involved in the production and therefore has been increasingly applied to assess the environmental burden. However, most LCA-related research studies have focused on the overall environmental impact of the entire sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…A green building is built with local and environmentally friendly materials and ensures the conservation of natural resources [5]. However, implementing green agricultural buildings still needs to be improved [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…A green building is built with local and environmentally friendly materials and ensures the conservation of natural resources [5]. However, implementing green agricultural buildings still needs to be improved [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Some efforts have been made to estimate the heat consumption in semi-closed buildings. Life Cycle Analysis, a recent tool used in this kind of assessment by Decano-Valentin et al [6], found that the energy used for climate control contributes to 86-96% of the gasses emitted, depending on the type, quantity, and energy source [7,8]. In addition, they used Building Energy Simulation (BES) tools to predict air temperature when using cooling or heating.…”
Section: Introductionmentioning
confidence: 99%